Voltammetric Detection of Diclofenac with Screen-printed Electrodes Based on Graphene and PVDF-Modified Graphene - Anita Grozdanov,1 Perica Paunović,1 Iva Dimitrievska,1 Ana Tomova (Kem Ind, 2024)
crucial aspects of modern healthcare and environmental management. Among the available sensing techniques, electrochemical methods, particularly those utilising screen-printed electrodes (SPEs) and different portable equipment have emerged as rapid, effective, sensitive, and inexpensive. This study focuses on the detection of the anti-inflammatory drug diclofenac in neutral media. Cyclic voltammetry measurements were conducted to identify diclofenac and determine the kinetics and electrochemical mechanism of its oxidation, along with assessing the surface characteristics of the employed SPEs. Graphene and modified graphene SPEs were explored as nanosensors for this purpose. The surface of the graphene SPE was modified using polyvinylidene fluoride, applied through a drop modification procedure. The morphology of the examined SPEs was observed by means of scanning electron microscope, while the electrolyte (0.1 g of diclofenac per litre of phosphate-buffered solution, pH = 7.4) was analysed using UV-Vis spectroscopy. The results indicate that the studied SPEs exhibit promising potential for the detection of diclofenac.
Keywords: Screen-printed electrodes, nanosensors, cyclic voltammetry, graphene, PVDF drop modification, diclofenac